2022
DOI: 10.1155/2022/4041402
|View full text |Cite
|
Sign up to set email alerts
|

Citrus unshiu Peel Attenuates Dextran Sulfate Sodium-Induced Ulcerative Colitis in Mice due to Modulation of the PI3K/Akt Signaling Pathway and MAPK and NF-κB

Abstract: Aim. Citrus unshiu peel has been used to treat various diseases in traditional East Asian medicine including Korea, and many studies have been reported regarding inflammatory diseases including ulcerative colitis (UC). However, the underlying mechanism by which Citrus unshiu peel modulates inflammation in UC remains unclear. Therefore, this study aimed to evaluate the therapeutic effect and underlying mechanism of Citrus unshiu peel water extract (CUP) for UC. Methods. The experiment for UC was conducted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Recent studies have reported that CUP downregulates the expression of pro-inflammatory cytokines by repressing the NF-κB signaling pathway in a macrophage cell line [ 63 , 64 ]. In addition, it is already known that water extracts of CUP decrease phospho-IκB in murine colon tissues [ 21 ]. Consistently, our data showed that the bioconversion of the CUP downregulated p50 and phospho-IκB, followed by the recovery of tight junction proteins, whereas the ethanol extracts of the CUP did not mediate this mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that CUP downregulates the expression of pro-inflammatory cytokines by repressing the NF-κB signaling pathway in a macrophage cell line [ 63 , 64 ]. In addition, it is already known that water extracts of CUP decrease phospho-IκB in murine colon tissues [ 21 ]. Consistently, our data showed that the bioconversion of the CUP downregulated p50 and phospho-IκB, followed by the recovery of tight junction proteins, whereas the ethanol extracts of the CUP did not mediate this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ethanol derivative of CUP ameliorated oxidative stress by suppressing nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 expression (NOX2) in a chemotherapy-induced neuropathic pain animal model [ 15 ] and decreasing the expression levels of pro-inflammatory cytokines, such as interleukin (IL)-6, interferon (IFN)-γ, and tumor necrosis factor-alpha (TNFα), in a type 2 diabetes and systemic inflammation mouse model [ 18 , 20 ]. Moreover, water extracts of CUP have been reported to attenuate dextran sulfate sodium-induced colitis by regulating the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway [ 21 ]. This prompted us to explore other pharmaceutically active products in CUP.…”
Section: Introductionmentioning
confidence: 99%
“…The JWZQS-H group (23.4 g/kg) had twice the concentration as the JWZQS-M group, and the JWZQS-L group (5.85 g/kg) had 0.5 times the concentration as the JWZQS-M group. The SASP (Shanghai Xinyi Co. LTD.) group 100 mg/kg SASP suspension by gavage [ 19 ]. Gavage was used to administer the corresponding volume of distilled water to the NT group.…”
Section: Methodsmentioning
confidence: 99%
“…염증성 장질환은 크게 궤양성 대장염(Ulcerative colitis)과 크론병(Crohn's Disease)으로 나뉘며 위장관 전체 및 장점막에서 염증의 완화와 악화가 반복되어 대장암의 발병률 을 상승시키는 특징을 가지고 있다 5 . 나타나는 증 상으로는 복통, 설사, 혈변 및 고름 등이 있으며, 이러한 증상들이 반복적으로 일어나 환자의 신체 적 및 정신적 건강에 심각한 영향을 미친다 6 . 지금 까지 염증성 장질환의 치료는 항염증제, 면역억제 제, steroid 및 corticosteroid 등의 약물을 사용하였 지만 약 20~40%의 환자들은 치료에 실패하거나 장기간 복용으로 인하여 부작용이 발생하게 된다 7,8 .…”
unclassified